(untitled) (Economic and Political Thought, 2017)
The aim of the article is to investigate comparatively integration policies of Estonia, Latvia and Lithuania as well as adaptation strategies of Russian-speakers in the Baltic states following the Baltic states’ independence. As a result, existing integration approaches, their determinants and effects will be outlined. In addition, the study addresses the issue of shaping civic and cultural identities of Russian speaking residents as a result of integration processes. The analysis is based on the assumption that the Baltic states have used different integration models as a consequence of various historical, political and social factors. The effectiveness of the integration process has depended on both the national strategy and the openness of the (titular and minority) ethnic groups to adaptation in the new environment.